Rare presentation of a Giant thrombosed aneurysm arising from the P2 segment of the right PCA in a 30-month-old child: A Case Report - Nahar, Shashank; Panchariya, Piyush (Nepal Journal of Neuroscience, 2025)
Brain aneurysms incidence is rare in children. Out of all intracranial aneurysms, posterior cerebral artery aneurysms (PCA) represent approximately 1% of all intracranial aneurysms Pediatric cerebral aneurysms are associated with a variety of systemic and intracranial disorders. We have reported a rare case of a giant thrombosed aneurysm arising from the P-2 segment of the right PCA in a 30-month-old child who presented to us. This case report was undertaken to understand the clinical presentation and radiological features of the PCA segment aneurysm in a pediatric age group so that it be early diagnosed and can be early managed to prevent pediatric mortality.